1993
DOI: 10.1002/etc.5620120116
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of fluoranthene in freshwater sediment toxicity tests

Abstract: To examine equilibrium‐partitioning model predictions of interstitial water concentrations of fluoranthene as part of the equilibrium‐partitioning (EqP) approach to sediment quality criteria development, the bioavailability (toxicity) of fluoranthene‐amended sediment (a nonpolar organic compound) to Hyalella azteca, Daphnia magna, and Chironomus tentans was determined. Fluoranthene was added to three freshwater sediments with similar organic carbon content (0.44‐0.50%). Although sediments were from divergent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 19 publications
3
44
1
Order By: Relevance
“…Verrhiest et al (2001) found in 10-day acute toxicity tests that phenanthrene and fluoranthene caused 50 % mortality of C. riparius at concentrations of 20 and 15 lg/g dw, respectively. The same magnitudes of the 10-day LC50 values (3 to 8.7 lg/g dw) were also reported for C. riparius exposed to fluoranthene (Suedel et al 1993). In addition to the potent of different PAHs, the divergence of LC50 values might be related to different organism stages and lengths of exposure periods used in testing: We used 24-h newly hatched midge larvae and a whole life cycle, whereas the other investigators used third-instar midges plus a 10-day exposure (Suedel et al 1993;Verrhiest et al 2001).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Verrhiest et al (2001) found in 10-day acute toxicity tests that phenanthrene and fluoranthene caused 50 % mortality of C. riparius at concentrations of 20 and 15 lg/g dw, respectively. The same magnitudes of the 10-day LC50 values (3 to 8.7 lg/g dw) were also reported for C. riparius exposed to fluoranthene (Suedel et al 1993). In addition to the potent of different PAHs, the divergence of LC50 values might be related to different organism stages and lengths of exposure periods used in testing: We used 24-h newly hatched midge larvae and a whole life cycle, whereas the other investigators used third-instar midges plus a 10-day exposure (Suedel et al 1993;Verrhiest et al 2001).…”
Section: Resultssupporting
confidence: 81%
“…The same magnitudes of the 10-day LC50 values (3 to 8.7 lg/g dw) were also reported for C. riparius exposed to fluoranthene (Suedel et al 1993). In addition to the potent of different PAHs, the divergence of LC50 values might be related to different organism stages and lengths of exposure periods used in testing: We used 24-h newly hatched midge larvae and a whole life cycle, whereas the other investigators used third-instar midges plus a 10-day exposure (Suedel et al 1993;Verrhiest et al 2001). Earlier, MacDonald et al (2000) reported that in freshwater ecosystems, the probable effect concentration of BaP was 76 lg/g OC, and BaP concentrations inducing the lowest and highest apparent effects were 160 and 360 lg/g OC, respectively.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Larval Chironomus riparius and Chironomus tentans have been demonstrated to tolerate a wide range of substrates from particle size ranges >90% silt and clay to 100% sand with no detrimental effects on survival or growth (Environment Canada, 1997 andSuedel et al 1993). However studies incorporating life-cycle and behavioural assessments (Sibley et al 1998) indicate that at least for C. tentans, survival of larvae was significantly reduced in a clay substrate (mean particle size 8 µm) as was time to first emergence.…”
Section: Sediment Requirementsmentioning
confidence: 99%
“…Of particular interest have been the effects of non-ionic surfactants on aquatic invertebrates and fishes in outdoor stream mesocosms (Figueroa 1995. Toxicological studies have encompassed a variety of topics including copper speciation and bioavailability (Suedel et al 1992, Deaver 1995, Sturgis 1995, response of Myriophyllum spicatum to controlled release formulation of fluridone (Wright 1993), and germination and early seedling growth of emergent wetland plants . An EPA-funded EPSCoR project involved a collaborative effort between the University of Mississippi, the University of Mississippi Medical Center, University of Southern Mississippi Gulf Coast Research Laboratory, Jackson State University, and Mississippi State University.…”
Section: Researchmentioning
confidence: 99%